Development of a prototype PET scanner with depth-of-interaction measurement using solid-state photomultiplier arrays and parallel readout electronics - Shao, Yiping (2014)
In this study, we developed a prototype animal PET by applying several novel technologies to use the solid-state photomultiplier (SSPM) arrays for measuring the depth-of-interaction (DOI) and improving imaging performance. Each PET detector has an 8×8 array of about 1.9×1.9×30.0 mm(3) lutetium-yttrium-oxyorthosilicate (LYSO) scintillators, with each end optically connected to a SSPM array (16-channel in a 4×4 matrix) through a light guide to enable continuous DOI measurement. Each SSPM has an active area of about 3×3 mm(2), and its output is read by a custom-developed application-specific-integrated-circuit (ASIC) to directly convert analog signals to digital timing pulses that encode the interaction information. These pulses are transferred to and be decoded by a field-programmable-gate-array (FPGA) based time-to-digital convertor for coincident event selection and data acquisition. The independent readout of each SSPM and the parallel signal process can significantly improve the signal-to-noise ratio and enable using flexible algorithms for different data processes. The prototype PET consists of two rotating detector panels on a portable gantry with four detectors in each panel to provide 16 mm axial and variable transaxial field-of-view (FOV) sizes. List-mode ordered-subset-expectation-maximization image reconstruction was implemented. The measured mean energy, coincidence timing, and DOI resolution for a crystal were about 17.6%, 2.8 ns, and 5.6 mm, respectively. The measured transaxial resolutions at the center of the FOV were 2.0 mm and 2.3 mm for images reconstructed with and without DOI, respectively. In addition, the resolutions across the FOV with DOI were substantially better than those without DOI. The quality of PET images of both a hot-rod phantom and mouse acquired with DOI was much higher than that of images obtained without DOI. This study demonstrates that SSPM arrays and advanced readout/processing electronics can be used to develop a practical DOI-measureable PET scanner.